Mobile Phone-Based Intervention in Hypertension Management. (7th April 2019) - Andre, Nobian; Wibawanti, Retno; Siswanto, Bambang Budi
Abstract : Hypertension is known as the major risk factor for cardiovascular mortality and morbidity. Antihypertensive agents are directed to prevent many of the harmful effects of elevated blood pressure, yet medication nonadherence hinders the effectiveness of these therapies. Nowadays the use of mobile phone has vastly spread among communities. The rapid adoption of smartphone technology creates a promising and interesting platform to overcome medication nonadherence. This review aimed to critically appraise whether mobile phone-based interventions are effective in increasing adherence in hypertensive patients. Literature searching was done in 3 databases: PubMed, Cochrane, and ProQuest. Findings were narrowed down using selection criteria. Relevant studies were to be critically appraised based on the guideline from Centre for Evidence-Based Medicine, Oxford University. We found that the reduction of blood pressure in participants who were given reminder through mobile phones was greater in comparison to control: systolic (94.4% vs 41.2%, p 0.003), diastolic (94.4% vs 76.5%, p0.04). Patients who were nonadherent at baseline benefit more from mobile phone-based intervention in comparison to adherent patients at baseline: RR 2.3 (95% CI: 1.4-4.4, p<0.001) vs RR 1.3 (95% CI: 1.0-1.6, p<0.05). In conclusion, mobile phone-based interventions were effective in increasing medication adherence in hypertensive patients. Clinical practice guidelines should consider this nonpharmacological method for a better blood pressure regulation.